Soil phosphorus fractions in an apple orchard with different weed managements (Research, Society and Development, 2020)
The presence of weeds in apple orchards affects the dynamics of nutrients in the soil, including phosphorus (P). The objective of this study was to evaluate changes in distribution of P fractions in the soil of an apple orchard under different weed managements. The experiment was conducted in an apple orchard in the municipality of Urubici, Santa Catarina, Brazil. The following treatments were implemented in 2011: no weed management (NWM), desiccation of weeds in the apple-tree row (DR), and hoeing of weeds in the apple-tree row (HR). Soil samples of the 0-2.5, 2.5-5, 5-10, 10-15 and 15-20 cm layers were collected in the apple-tree rows at 24 months after the implementation of the experiment. The samples were subjected to chemical fractionation of P, obtaining the following fractions: PiAER, PiNaHCO3, PoNaHCO3, PiNaOH, PoNaOH, PiHCl, PiNaOH05, PoNaOH05, and Presidual. The presence of weeds increased the contents of the following soil P fractions in the surface layers: PiAER, PiNaHCO3, and PoNaHCO3, which are bioavailable to plants. A higher proportion of organic forms of P in the soil was found when the weeds were hoed; these fractions can be mineralized and used for nutrition of apple trees when labile P forms are exhausted.